2019
DOI: 10.1177/1362361319841197
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic alliance in cognitive-behavioral therapy for school-aged children with autism and clinical anxiety

Abstract: Little is known about the alliance between therapists and children with autism spectrum disorder who are receiving psychological therapies in outpatient treatment settings. This study examined the therapeutic alliance in children with autism spectrum disorder and clinical anxiety, who were receiving cognitive behavioral therapy in a randomized, controlled trial. The Therapeutic Alliance Scale for Children was administered to a sample of children and youth with autism spectrum disorder and anxiety ( N = 64; age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 44 publications
2
39
2
4
Order By: Relevance
“…Children with autism may have challenges with perspective taking and following social norms and cues (Davidson et al, ), which may impact the therapeutic relationship. While ample research suggests that these deficits in social skills affect the ability to develop and maintain relationships (Laugeson, Gantman, Kapp, Orenski, & Ellingsen, ; Stichter et al, ), our findings align with those of recent studies and show that working relationships with child clients with autism and their family members may be reliably measured (Klebanoff et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Children with autism may have challenges with perspective taking and following social norms and cues (Davidson et al, ), which may impact the therapeutic relationship. While ample research suggests that these deficits in social skills affect the ability to develop and maintain relationships (Laugeson, Gantman, Kapp, Orenski, & Ellingsen, ; Stichter et al, ), our findings align with those of recent studies and show that working relationships with child clients with autism and their family members may be reliably measured (Klebanoff et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, researchers have begun to examine TA in cognitive–behavioural interventions for children with autism (Brown et al, ; Klebanoff, Rosenau, & Wood, ). Cognitive behaviour therapy (CBT) is considered a “promising” evidence‐based intervention for children with autism to address associated emotional problems (Wong et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small qualitative study, Houlding (2014) found that mothers of children with ASD ( N = 3) perceived strong therapeutic alliance as essential to their and their child’s participation in CBT for obsessive compulsive disorder (OCD). Furthermore, among children who participated in modular CBT for anxiety, Klebanoff (2015) found that therapist alliance ratings were weaker for youth with versus without ASD, but still positively associated with anxiety improvement in the ASD group. These studies suggest connections between alliance and CBT response in children with ASD that warrant further investigation.…”
Section: Introductionmentioning
confidence: 97%
“…En estudios previos, si bien la función Instruccional ha sido señalada como quizás la más importante del EPT por sus vínculos con la alianza terapéutica (Corbella et al, 2007), ha sido también cuestionada por su escaso apoyo en los estudios psicométricos (Silva y Guedes, 2016). Por tal motivo debería continuar estudiándose, especialmente en el tratamiento de pacientes con TEA, porque la alianza terapéutica también desempeña un papel central (Brown et al, 2015;Goodman, Chung, Fischel yAthey-Lloyd, 2017;Klebanoff, 2015).…”
Section: Discussionunclassified